Side-Effects of campaign finance reform - Matthias Dahm; Nicolás Porteiro (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2005)
Since campaign finance reform is usually motivated by the concern that existing legislation can not effectively prevent campaign contributions to 'buy favors', this paper assumes that contributions influence political decisions. But, given that it is also widely recognized that interest groups achieve influence by providing political decision makers with policy relevant information, we also assume that lobbies engage in non-negligible informational lobbying. We focus on a single political decision to be taken and offer a simple model in which the optimal influence strategy is a mixture of both lobbying instruments. Our main result is to show that campaign finance reform may have important side-effects: It may deter informational lobbying so that less policy relevant information is available and as a result political decisions become less efficient.
Keywords: C72; D72; 330; party and candidate financing; lobbying; interest groups; experts; information transmission; contributions; influence; political decision making process; Wahlkampffinanzierung; Interessenpolitik; Spieltheorie; Politische Entscheidung; Theorie